Praktek Manajemen Sumber Daya Manusia Berbasis Kompetensi pada Organisasi Sektor Publik - Alfian Rosiadi; Margono Setiawan; Wahdiyat Moko (Jurnal Manajemen dan Kewirausahaan, 2018)
This study aims to explore human resource management practice based on competency in public sector organizations by taking case studies at the Government of Tulungagung Regency. The human resource management practice based on competency  in public sector organizations have been conducted through the application of Law no. 5/2014 about the State Civil Apparatus. This study uses a qualitative approach where data obtained through semi-structured in-depth interviews of 7 (seven) research informants which authorized in public sector human resource management. The results of data analysis shows that the implementation of human resources management practice based on competency is found in the recruitment and selection process, career management and competency development. But human resources management  practice  on competency is not  found  in the performance appraisal.  https://doi.org/10.26905/jmdk.v6i2.2208